Learning Methods And Digital Literacy As Predictors Of Higher-Order Thinking Skills - Sri Puji Lestari; Otib Satibi Hidayat; Sidik Puryanto (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
This study explores how learning methods and digital literacy influence students’ higher-order thinking skills within the context of natural and social science instruction at SDN Muktiwari 02. Developing higher-order thinking skills (HOTS) is imperative, given that these competencies empower students to navigate and solve problems arising in daily life. Students’ daily problems are inseparable from the transformation that has been reformed by integrating digital literacy. Therefore, the treatment for the control class and the experimental class was divided into two groups: the control class used conventional methods, and the experimental class used PjBL and digital literacy. This treatment resulted in a paired samples t-test using SPSS 27. The analysis of SPSS 27 results revealed a difference in pretest HOTS scores for students using conventional strategies and digital literacy, with an average score of 69.07 and a posttest score of 77.80, with the Ha decision accepted. There was a difference in pretest HOTS scores for students using PjBL strategies and digital literacy, with an average score of 69.07 and a posttest score of 85.20, with the Ha decision accepted. The PjBL learning model has a very significant or higher influence on higher-order thinking skills (HOTS) compared to conventional learning.